Aqueous solution behavior of comb‐shaped poly(2‐ethyl‐2‐oxazoline). Issue 1 (29th August 2012) - Weber, Christine; Rogers, Sarah; Vollrath, Antje; Hoeppener, Stephanie; Rudolph, Tobias; Fritz, Nicole; Hoogenboom, Richard; Schubert, Ulrich S.
Abstract A series of comb polymers consisting of a methacrylate backbone and poly(2‐ethyl‐2‐oxazoline) (PEtOx) side chains was synthesized by a combination of cationic ring‐opening polymerization and reversible addition–fragmentation chain transfer polymerization. Small‐angle neutron scattering (SANS) studies revealed a transition from an ellipsoidal to a cylindrical conformation in D2O around a backbone degree of polymerization of 30. Comb‐shaped PEtOx has lowered Tg values but a similar elution behavior in liquid chromatography under critical conditions in comparison to its linear analog was observed. The lower critical solution temperature behavior of the polymers was investigated by turbidimetry, dynamic light scattering, transmission electron microscopy, and SANS revealing decreasing Tcp in aqueous solution with increasing molar mass, the presence of very few aggregated structures below Tcp, a contraction of the macromolecules at temperatures 5 °C above Tcp but no severe conformational change of the cylindrical structure. In addition, the phase diagram including cloud point and coexistence curve was developed showing an LCST of 75 °C of the binary mixture poly[oligo(2‐ethyl‐2‐oxazoline)methacrylate]/water. © 2012 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2013